1985
DOI: 10.1002/kin.550170206
|View full text |Cite
|
Sign up to set email alerts
|

An outdoor smog chamber and modeling study of toluene–NOx photooxidation

Abstract: An experimental investigation of the gas-phase photooxidation of toluene-NO,-air mixtures a t part-per-million concentrations has been carried out in a 6B-m3, outdoor smog chamber to assess our understanding of the atmospheric chemistr,y of toluene. In addition, six CO-NO,-air irradiations were conducted to characterize the chamber with regard to any wall radical sources. Measured parameters in the toluene-NO, experiments included 0 3 , NO, NO,, HN03, peroxyacetyl nitrate (PAN), CO, toluene, benzaldehyde, o-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 29 publications
3
70
1
1
Order By: Relevance
“…The ring-retaining products observed in this work have been previously reported from several studies [8,9,11,12,15,16,18-21, 23,24,27]. For benzaldehyde, the present formation yield is in reasonable agreement with those of Atkinson et al [15,19], Shepson et al [20), Leone et al [23], Bandow et al [24], and Gery et al [27]. The benzaldehyde yields reported by Spicer and Jones [8] and O'Brien et al [ll] are widely divergent and must be judged to be incorrect.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The ring-retaining products observed in this work have been previously reported from several studies [8,9,11,12,15,16,18-21, 23,24,27]. For benzaldehyde, the present formation yield is in reasonable agreement with those of Atkinson et al [15,19], Shepson et al [20), Leone et al [23], Bandow et al [24], and Gery et al [27]. The benzaldehyde yields reported by Spicer and Jones [8] and O'Brien et al [ll] are widely divergent and must be judged to be incorrect.…”
Section: Discussionsupporting
confidence: 95%
“…The formation of the cresol isomers has been reported previously [8,9,11,12,15,16,19,20,23,27], although, as in this work, m-+ p-cresol Nitrotoluenes have been identified as products of the OH radical reaction with toluene under simulated atmospheric conditions in several previous studies [9,12,15,21,23,27] (in some of these studies, only m-nitrotoluene was reported [ 15,231). Hoshino et al [9] observed m-and p-nitrotoluene, but no o-nitrotoluene, with the p-nitrotoluene yield generally being less than that of the m-nitrotoluene isomer.…”
Section: Discussionmentioning
confidence: 63%
“…Smog chambers were initially constructed for developing and evaluating atmospheric gasphase chemical mechanisms or models for predicting secondary pollutants (Akimoto et al, 1979;Carter et al, 1982;Jeffries et al, 1982Jeffries et al, , 1985. In the mid-1980s, Seinfeld and colleagues at the California Institute of Technology in Pasadena developed a 65 m 3 outdoor chamber made of fluorinated ethylene propylene (FEP) Teflon film to study the aerosol formation from gas-phase precursors such as aromatic and biogenic hydrocarbons (Leone et al, 1985;Stern et al, 1987). In the subsequent three decades, outdoor and indoor chambers have been widely used to study formation of secondary pollutants such as ozone (Hess et al, 1992;Simonaitis et al, 1997;Carter, 2000;Dodge, 2000) and secondary organic aerosols (SOA) (Odum et al, 1996,Paulsen et al, 2005Rollins et al, 2009) and evolution of SOA (Donahue et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many simulation experiments on SOA formation have been carried out in large outdoor chambers (Leone et al, 1985;Stern et al, 1987;Pandis et al, 1991;Johnson et al, 2004;Martín-Reviejo and Wirtz, 2005;Rollins et al, 2009). However, diurnal variations of the actinic flux and temperature make it difficult to model experimental data and to reproduce the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate kinetic measurements were possible due to the high pipe aspect ratios, which encouraged a high degree of plug flow behavior (Keyser, 1984). The design of these miniature tubular reactors, with volumes on the order of a few cm 3 , was different from that of significantly larger, batch-type or semi-continuous type well-mixed reactors, with volumes on the order of several m 3 , built to understand aerosol formation in the troposphere (Crump et al, 1982;Crump and Seinfeld, 1980;Leone et al, 1985). To study aerosol formation and growth chemistry, the dynamics of atmospheric circulation and transport needed to be excluded.…”
Section: Introductionmentioning
confidence: 99%